'Bold Liberals Who Fought for the Cause of Freedom': The German Reception of the Graphic Satires of James Gillray and Thomas Rowlandson at the Fin De Siècle (1895–1908). Issue 2 (4th May 2019) - Potter, Matthew C.
Abstract : This article explores the reception of the work of James Gillray and Thomas Rowlandson in Germany in the long nineteenth century, within the contexts of evolving art historical studies and nationalist cultural policies during the period. The German-language art historical writings of fin-de-siècle critics (two from Germany – Richard Muther and Hans Wolfgang Singer – and two from the Low Countries – Charles Polydore de Mont and Jan Veth) demonstrate how these authors used historical examples of British graphic satire to promote modern liberal agendas of protest and internationalism in opposition to the narrow nationalism of the Prussian-led Kaiserreich (the German Empire, 1871–1918).